Revisiting Modernity and the Holocaust
1 online resource
Keywords: "Zygmunt Bauman's Modernity and the Holocaust is a decisive text of intellectual reflection after Auschwitz, in which Bauman rejected the idea that the Holocaust represented the polar opposite of modernity and saw it instead as its dark potentiality. Bringing together leading scholars from across disciplines, this volume offers the first set of focused and critical commentaries on this classic work of social theory, evaluating its ongoing contribution to scholarship in the social sciences and humanities. Addressing the core messages of Modernity and the Holocaust that continue to sound amidst the convulsions of the present, the chapters situate Bauman's volume in the social, cultural and academic context of its genesis, and considers its role in the complex processes of Holocaust memorialisation. Offering extensions of Bauman's thesis to lesser-known and under-theorised events of mass violence, and also considering the significance of Janina Bauman's writings in their own right, this volume will appeal to scholars of sociology, intellectual history, Holocaust and genocide studies, moral philosophy, memory studies, and cultural theory"--